Search for resonances decaying into top-quark pairs using fully hadronic decays in $pp$ collisions with ATLAS at $\sqrt{s}=7$ TeV - ATLAS collaboration (2910 authors); Aguilar-Saavedra, Juan Antonio; Amor Dos Santos, Susana Patricia; Anjos, Nuno; Cantrill, Robert; Carvalho, João; Castro, Nuno Filipe; Conde Muiño, Patricia; Da Cunha Sargedas De Sousa, Mario Jose; Do Valle Wemans, André; Fiolhais, Miguel; Galhardo, Bruno; et al. (My University, 2012)
A search for resonances produced in 7 TeV proton-proton collisions and decaying into top-quark pairs is described. In this Letter events where the top-quark decay produces two massive jets with large transverse momenta recorded with the ATLAS detector at the Large Hadron Collider are considered. Two techniques that rely on jet substructure are used to separate top-quark jets from those arising from light quarks and gluons. In addition, each massive jet is required to have evidence of an associated bottom-quark decay. The data are consistent with the Standard Model, and limits can be set on the production cross section times branching fraction of a Z' boson and a Kaluza-Klein gluon resonance. These limits exclude, at the 95% credibility level, Z' bosons with masses 0.70-1.00 TeV as well as 1.28-1.32 TeV and Kaluza-Klein gluons with masses 0.70-1.62 TeV.